Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/toxins14050358
|View full text |Cite
|
Sign up to set email alerts
|

Venomics of the Central European Myrmicine Ants Myrmica rubra and Myrmica ruginodis

Abstract: Animal venoms are a rich source of novel biomolecules with potential applications in medicine and agriculture. Ants are one of the most species-rich lineages of venomous animals. However, only a fraction of their biodiversity has been studied so far. Here, we investigated the venom components of two myrmicine (subfamily Myrmicinae) ants: Myrmica rubra and Myrmica ruginodis. We applied a venomics workflow based on proteotranscriptomics and found that the venoms of both species are composed of several protein cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 88 publications
(116 reference statements)
1
12
0
Order By: Relevance
“…In order to fully characterize the venoms of aculeates, a comparative study of venomgland transcriptomes and proteomes is necessary. In recent years, the number of studies that included these data for hymenopterans has increased, but in the face of the enormous diversity of the order, it is clear that the research community has only started to scratch the surface of what there is to be discovered [ 62 , 78 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. One interesting aspect of our own contribution to this enormous task is that the transcripts we identified from the venom gland of A. mellifera were found to have nearly identical sequences to other A. mellifera venom proteins which are available in the Uniprot database ( Figure 2 ) and those identified by Koludarov et al [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to fully characterize the venoms of aculeates, a comparative study of venomgland transcriptomes and proteomes is necessary. In recent years, the number of studies that included these data for hymenopterans has increased, but in the face of the enormous diversity of the order, it is clear that the research community has only started to scratch the surface of what there is to be discovered [ 62 , 78 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. One interesting aspect of our own contribution to this enormous task is that the transcripts we identified from the venom gland of A. mellifera were found to have nearly identical sequences to other A. mellifera venom proteins which are available in the Uniprot database ( Figure 2 ) and those identified by Koludarov et al [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…The venom composition of ants has received less attention with limited publication to date [ 10 , 11 , 12 , 13 , 14 ]. These previously published studies revealed the large diversity of venom components from each species based on the transcriptomic, proteomic, or proteo-transcriptomic approach [ 10 , 13 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, alkaloids in the venom of ants have been relatively well-studied [ 9 ], while other venomous chemical compounds and proteinaceous venoms remain largely unveiled. Proteinaceous venom components have only been deciphered in a limited number of ants from several subfamilies including Ectatomminae, Myrmeciinae, Myrmicinae, Ponerinae, Paraponerinae, and Pseudomyrmecinae, mostly focused on emblematic species [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The characterization of venom components from more ant species belonging to diverse subfamilies will contribute to a better understanding of the evolution of ant venoms and facilitate their applications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, thanks to the high sensitivity of modern methods, venom components can now be analyzed using limited amounts of sample material. This has allowed the inclusion of species that were formerly either too rare for the collection of meaningful amounts of venom, or too small to deliver sufficient venom yields ( de Graaf et al, 2009 ; Bouzid et al, 2014 ; Lewis Ames et al, 2016 ; Walker et al, 2018 ; Walker et al, 2021 ; Casewell et al, 2019 ; Krämer et al, 2019 ; Schmidt et al, 2019 ; Lüddecke et al, 2020 ; Lüddecke et al, 2022 ; Hurka et al, 2022 ; von Reumont et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%